Design of LPG Leakage Detection Device using MQ-2 Sensor Equipped with Hazard Warning System - Fadila Maiza; Suratun Nafisah; Khansa Salsabila Suhaimi; Ahmad Fahri Fahrezi (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2024)
The use of liquefied petroleum gas (LPG) as household fuel in Indonesia has increased because it has greater heating power and equipment efficiency than other fuels. LPG is flammable and can explode if a leakage occurs and is exposed to a fire source. Therefore, explosions can be anticipated by installing a gas leakage detector equipped with a danger warning feature called Tor-G (LPG Detector) based on the NodeMCU ESP8266 microcontroller using an MQ-2 sensor with a buzzer and LED as a danger warning feature. Tor-G can detect when a gas leakage occurs and provides a danger signal in the form of a sound from a buzzer which can be heard several meters away by the homeowner so that an explosion can be anticipated quickly. This research carried out four tests: the sensor accuracy test, the sensor responsiveness test, the distance between the sensor and the leakage source test, and the responsiveness of the buzzer and LED test. The results of the tests show that the sensor only detects the LPG. The sensor readings are accurate since the value of Rs/Ro on the Tor-G is not much different from that of Rs/Ro on the datasheet, thus producing an error value in the 0% -0.08% range. The ideal installation position of the Tor-G is 75 cm from the gas cylinder and the danger warning system from the buzzer and red LED lights up within 18.88 seconds.